Analisis Dampak Kredit Mikro Terhadap Perkembangan Usaha di Kabupaten Tapanuli Tengah (Studi Kasus : Nasabah KSP CU Pardomuan Pakkat Cabang Barus). - Nur Aisyah Pasaribu; Yenni Sofiana Tambunan; Kaharudddin Simamora (CV. ALIM'SPUBLISHING, 2023)
Nur Aisyah Pasaribu. 2022. Analysis of the Impact of Micro Credit on the Development of Micro Enterprises in Central Tapanuli Regency (Case Study of Customers of Ksp CU Pardomuan Pakkat Barus Branch) . Thesis : Corporate Management Study Program STIE Al Washliyah Sibolga Central Tapanuli. This study aims to determine the impact of micro-credit on the development of micro-enterprises in Central Tapanuli Regency (Case Study of Customers of Ksp CU Pardomuan Pakkat Barus Branch). The population and sample of this research are Ksp CU customers having their address in Barus sub-district as many as 30 people. The research method used is a quantitative method with a descriptive approach, the data collection technique is a questionnaire using a Likert scale while the test used is Data Analysis Test. The results showed that the impact of Micro credit (X) on Micro Business Development (Y) was tcount 3,768 > ttable 2,059, it means that the null hypothesis (H0) is rejected and it can be concluded that microcredit (X) partially has a positive effect on development. micro enterprise (Y). With the regression equation Y = 20.309 - 0.543 X, this means that there is an influence on the dependent variable (Development of micro-enterprises) determined by the independent variable (micro-credit), with a coefficient of determination of 0.336, practically it can be said that the contribution of micro-credit (X) on the development of micro-enterprises (Y) is 33.6%, the remaining 66.4% is influenced by other variables not examined in this study.